Measuring Mechanical Properties and Simulating the Creep Behavior of Wild Cane Stem using Burger-Voigt Model - M Porabolghasem (Ferdowsi University of Mashhad, 2021)
IntroductionKnowledge of mechanical and viscoelastic properties of agricultural material will be helpful in the transportation and processing of these materials. Giant reed grass, also known as wild cane, is a tall, perennial, bamboo-like, grass that grows in wet areas.  The giant reed grass can flourish in a wide variety of soils, including coarse sands, gravelly soil, heavy clay, and river sediment.  This grass attains heights of 7 m and once established the stems can reach a thickness close to 3 cm.  The stems of giant reed grass are used for different purposes. Traditionally the stems are used in the villages for fencing, roofing, and producing handcrafts. The modern uses of the giant reed stems include plywood, composites panels and paper production. The giant reed stems are not uniform and are made from many nodes. The number of nodes and the distance between nodes can affect the mechanical properties of the stems. In order to attain a suitable use of the stems in various industries, the physical and mechanical properties of the stems must be determined. Knowledge of mechanical and viscoelastic properties of agricultural material will be helpful in transportation and processing of these materials. The purpose of this research was to determine some relevant mechanical properties of the stems of giant reed grass with different nodes and moisture contents.Materials and MethodsIn this research, different mechanical and viscoelastic tests were performed on the stems of cane at various levels of moisture and number of nodes. The Burger-Voigt model with different number of elements was also used to model the creep behaviors of the stems. The cane stems were cut and divided to three groups of two, four, and six-node stems. The moisture contents of the stems were adjusted to three levels of 30, 40 and 50% (w.b.). After preparing the stems the mechanical tests were performed using an Instron testing machine with a three-point support. The creep tests were done by hanging a 10 kg weight at the middle of each stem. The experiments were done using factorial tests based on completely randomized design. The Young module, toughness, and the yield points of the stems were measured by the three-point method. These parameters were obtained from the stress-strain curves of the three-point compression bending tests. The results showed that the Young module was affected by both moisture and the number of nodes, but there were no interaction effects. The creeps of the stems under 10 kg loading were modeled using 3 to 5 elements Burger-Voigt models. In these models a combination of springs and dashpots are used to represent the stems. The curve fitting was performed using the MATLAB software and the goodness of fitness was verified using the fitted curves and calculating the coefficient of determinations.Results and DiscussionThe results by investigating the graphs and the ANOVA tests showed that the Young module was significantly affected by both moisture and the number of nodes. The obtained Young module for cane stem ranged from 572-1268 MPa. Both yield point and toughness were affected by both moisture and the number of nodes and their values were 65-250 N and 0.016-0.132 J.m-3, respectively. The creep test results indicated that the maximum deformation and maximum time for of the interaction of the two factors was insignificant. The maximum deformations ranged from 2.1-42.5 mm, and the maximum time for reaching the final deformation was 12.5-75 minutes for various moistures and the number of nodes combinations and showed that the 5-element Burger was best for explaining the viscoelastic behavior of cane stems (R2>0.97).ConclusionsIn this research, some mechanical properties of the giant reed grass stems were measured and the creep behavior of the stem was modeled using 3-5 elements Burger-Voigt models. The results indicated a decrease in the Young module of the stems with increase with moisture content and increase in the Young module with increase in the number of nodes. On the other hand, the elongation of the stems increased with both number of the nodes and the level of moisture. The 5-element Burger-Voigt model was best fitted to the creep data.